Os direitos tradicionais de propriedade da terra e a gestão das florestas tropicais: o caso do Gabão - Onanga, Prisca (2001)
This dissertation examines to what extent traditional populations in rural Gabon, Africa, are a threat to deforestation. Using a case study, the dissertation examines how local populations manage their forest resources through decisions that are based on traditional rules of behavior. The study examines how these rules and the way they change depend on traditional property rights over natural resources and land, the forest politics of Gabon, and the social and economic organization of the farming populations. Finally, the dissertation shows evidence that the sustainable development of the forests is compatible with traditional rules of decision, as well as that Westem law based on individual property rights and concessions can help or undermine the protection ofthe forests.